Rectal Nonsteroidal Anti-Inflammatory Drugs for Endoscopic Retrograde Cholangiopancreatography Postoperative Pancreatitis Prevention: A Network Meta-Analysis. Issue 4 (April 2020) - Yang, Jiahui; Wang, Wancong; Liu, Chuan; Zhao, Yan; Ren, Mudan; He, Shuixiang
Abstract : Background: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most common complication of ERCP procedure. Nonsteroidal anti-inflammatory drugs (NSAIDs) are reported to be one protective pharmacological agent with great efficacy regarding this complication. Recently, more trails have addressed this issue and some inconsistent results appeared. Therefore, this study aims to evaluate the efficacy and safety of different rectal NSAIDs schemes to prevent PEP. Materials and Methods: Eligible studies published on PubMed, the Cochrane Library, Embase, Web of Science before November 2018 were reviewed, and those which met the inclusion criteria were included in the analysis. The preventions were divided as placebo/no treatment, post-ERCP rectal diclofenac, pre-ERCP rectal diclofenac, post-ERCP rectal indomethacin, pre-ERCP rectal indomethacin, indomethacin using during ERCP, and pre-ERCP rectal naproxen. The main outcomes included the incidence of PEP and its severity. Other complications were also analyzed. Results: A total of 23 randomized controlled trials were included. The results of network meta-analysis illustrated that compared with the control, post-ERCP rectal diclofenac, pre-ERCP rectal diclofenac, and indomethacin were significantly associated with lower incidences of PEP. Moreover, it is notable that pre-ERCP rectal NSAIDs might reduce the severity of pancreatitis. Also, rectal NSAIDs may lead to less occurrence of asymptomatic hyperamylasemia. On the basis of the clustered ranking, pre-ERCP diclofenac appeared to be the superior intervention for PEP with satisfying efficacy. Conclusions: The present study showed that pre-ERCP diclofenac is the optimal prevention method for PEP. However, more high quality head-to-head randomized controlled trials and observational studies are expected in the future.